Coping Stress Santri Asrama Bahasa Pusat Putri Ditinjau dari Tahap Perkembangan Remaja dan Dewasa Awal di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo - Finanin Nur Indana; Fitri Husnun Halimah (Jurnal Multidisiplin Ibrahimy, 2024)
The house of Abraham was a place of worship, a place of peace, a place of peace, a place of peace, and a place of honor..24 hours a day., The santri lived in the cottage with all the routine and duties in the cottage and in school.With a densely packed routine and activities performed by the santrian, Makes the santri have a higher stress level..However, With a good coping for the santri when solving the problem.Lets the santri have a good stress level.The research was intended to find out coping stress in the princess-speaking santri dorm at the boarding house of kastren salafiyah syafi yaah sukorejo cababondo.Method used is descriptive quantity.Populations in this study are santri in the central language of a teenage and adult daughter., obtained a sample of 140 of 216 people using a proportionate stratified random trampling technique. Studies show that the tendency to coping stress on the princess central language hostel station in the motion focused dimension of 72.9 % (102 student), on dimension of focused coping 66.4 % (93 student). Based on the results of the independent test samples sig. (2-tailed), 033<0.05 points to a significant difference between adolescent and adult development.Coping stress can be used as one way to reduce stress. Thus, The higher the coping is done, Then it's going to be less stress levels.